Exploring the Wenzhou Spirit in Chinese Diet: A Comparative Study of Regional Diversity and Diaspora Adaptation - Ni, Jiaze (Transactions on Environment, Energy and Earth Sciences, 2024)
This study examines how the "Wenzhou Spirit" influences dietary practices in the Wenzhou region and its global diaspora. The Wenzhou Spirit, known for its entrepreneurial drive and cultural resilience, shapes the region’s culinary traditions, which emphasize fresh, local ingredients and traditional methods. By comparing these practices within China and among the diaspora, the research highlights the balance between preserving cultural heritage and adapting to new environments. Interviews with Wenzhou locals and diaspora members reveal how these culinary traditions evolve, demonstrating the Wenzhou Spirit’s role in sustaining and spreading the region’s food culture globally.